Rancang Bangun Manipulator Lengan Robot 4 Derajat Kebebasan untuk Mengangkat Telur Ayam Broiler Menggunakan Algoritma Levenberg-Marquardt - Aman, Khairul; Asran, Asran; Fariadi, Dedi; Muthalib, Muchlis Abdul; Yusdartono, Habib Muharry (Journal of Applied Electrical Engineering, 2024)
The robotic arm, wirelessly controlled via Bluetooth and an Android device, allows users to manipulate objects without direct contact. The Force Sensitive Resistor (FSR) sensor is employed to measure the gripping force of the gripper, while the Levenberg-Marquardt Algorithm ensures precise movement control. For delicate objects such as broiler chicken eggs, the gripper is designed to stop automatically upon reaching a threshold value of 552, which was obtained from an average of 11 manual data collections. When the FSR sensor detects a force exceeding this threshold, the algorithm halts the gripper to prevent damage to the object. From 10 experimental trials, the system demonstrated a 100% success rate, with the gripper stopping precisely without causing any damage to the eggs. The variation in pressure across different objects is believed to be due to differences in eggshell thickness or continuous sensor fluctuations during testing.